Conference report (including non-peer reviewed articles) of the 13th Nordic Conference on Reindeer and Reindeer Husbandry Research, 23-25 August 2004, Røros, Norway. - Haugerud (Editor), Rolf Egil (Rangifer, 2005)
The 13th Nordic Conference on Reindeer and Reindeer Husbandry Research gathered 75 participants representing the sciences, husbandry, management and education. The main topics were South Sami reindeer husbandry, the concession reindeer husbandry in South Norway and future aspects of reindeer industry. The main focus and other themes as well were discussed in lectures and poster presentations. The conference was arranged by Nordic Council for Reindeer Husbandry Research (NOR) in cooperation with Centre for Sami Studies, University of Tromsø. The conference was held in the South Sami area in the town of Røros. Rangifer Report No. 9, 2004, was published for the conference and included conference programme and abstracts. A proceedings report with articles based on the conference' lectures, is published here in this issue of Rangifer Report.
Keywords: NOR; conference; 2004; Røros; reindeer husbandry research